2011
DOI: 10.1002/jpln.201000264
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of pepper are affected by humic substances derived from composted sludge

Abstract: A greenhouse experiment was conducted to evaluate the effects of humic substances extracted from composted sewage sludge on growth, phenological development, and photosynthetic activity of pepper (Capsicum annuum L. cv. Piquillo) plants. Humic substances derived from composted sludge (HSS) were compared with those derived from leonardite (HSL). Two doses of both humic substances were assayed (200 and 500 mg C [L substrate] -1 ) and compared with a control (C). HSS showed higher nitrogen content and a higher pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 39 publications
5
36
1
3
Order By: Relevance
“…In particular, previous studies reported the improvement of pepper plant biomass and yield by either natural biostimulants [26] or humic substances from composted sludge [13]. Accordingly, RG and AH application to plants resulted in increased leaf biomass and weight of green peppers at the flowering stage, as well as in increased red pepper number and growth at maturity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In particular, previous studies reported the improvement of pepper plant biomass and yield by either natural biostimulants [26] or humic substances from composted sludge [13]. Accordingly, RG and AH application to plants resulted in increased leaf biomass and weight of green peppers at the flowering stage, as well as in increased red pepper number and growth at maturity.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, they decrease the use of mineral fertilizers by increasing the amount of micro-and macro-nutrients taken up by plants, positively influencing root morphology and plant growth [9,10]. They also display hormone-like activity and influence plant metabolism by interacting with biochemical processes and physiological mechanisms, such as glycolysis and nitrogen assimilation [11,[12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Pinheiro et al (2010), increase in HA concentration in nutrient solution drastically reduced accumulation of Fe, Cu, and Zn; however, for Mn, this effect was not so pronounced as for Fe, Cu, Zn and B; depending on the source, Mn accumulation improves when the concentration of 10 mg L -1 C-HA is used. Application of HA increasing macronutrient accumulation in plants is shown in greater magnitude for N, P, K, and Ca (AZCONA et al, 2011;EKINCI et al, 2015;MELO et al 2015;TAVARES et al, 2017), whereas, for S and Mg, this effect may be small or null (AZCONA et al, 2011;PINHEIRO et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to Rose et al (2014), the source of HA modulates its effect on plants by changing pH, EC, nutrient concentrations, presence of organic acids, molecular weight, presence of hormones, and other substances that play an important role in plant physiological and biochemical processes, mainly those HA derived from composted sources (MARTINEZ-BALMORI et al, 2014;ROSE et al, 2014). The effect of the HA source is dependent on the concentration used, which affects nutrient acquisition by plants (AZCONA et al, 2011), considered that compostderived HA are more chemically bioactive and requires lower optimal concentrations to positively affect plants (GARCÍA et al, 2016;ROSE et al, 2014).…”
Section: Introductionmentioning
confidence: 99%